2018
DOI: 10.1089/neu.2016.4871
|View full text |Cite
|
Sign up to set email alerts
|

Intranasally Delivered Wnt3a Improves Functional Recovery after Traumatic Brain Injury by Modulating Autophagic, Apoptotic, and Regenerative Pathways in the Mouse Brain

Abstract: Traumatic brain injury (TBI) is a prevalent disorder, but no effective therapies currently exist. An underlying pathophysiology of TBI includes the pathological elevation of autophagy. β-Catenin, a downstream mediator of the canonical Wnt pathway, is a repressor of autophagy. The Wnt/β-catenin pathway plays a crucial role in cell proliferation and neuronal plasticity/repair in the adult brain. We hypothesized that activation of this pathway could promote neuroprotection and neural regeneration following TBI. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 67 publications
1
33
0
Order By: Relevance
“…Both the STING and type-I IFN pathways have emerged as key players in autophagy activation in cellular and other disease models [ 47 , 51 ] but their interaction and regulation following brain injury is unknown. Our results demonstrated increased expression of autophagy markers in both WT and STING −/− mice at 2 h and 24 h after TBI as compared to their sham controls validating our CCI model in inducing autophagy as previously reported [ 44 , 73 , 74 ]. Interestingly, after CCI, we observed increased and sustained expression of LC3 and p62 in STING −/− brains as compared to their WT counterparts.…”
Section: Discussionsupporting
confidence: 90%
“…Both the STING and type-I IFN pathways have emerged as key players in autophagy activation in cellular and other disease models [ 47 , 51 ] but their interaction and regulation following brain injury is unknown. Our results demonstrated increased expression of autophagy markers in both WT and STING −/− mice at 2 h and 24 h after TBI as compared to their sham controls validating our CCI model in inducing autophagy as previously reported [ 44 , 73 , 74 ]. Interestingly, after CCI, we observed increased and sustained expression of LC3 and p62 in STING −/− brains as compared to their WT counterparts.…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, the cortical phenotype observed following Atg5 silencing is fully rescued by β-catenin knockdown ( Lv et al, 2014 ). On the other hand, it has been reported that Wnt3A decreases autophagy in mature neurons after traumatic brain injury while increasing hippocampal neurogenesis ( Zhang et al, 2018a ). In contrast, Wnt3A increases autophagy in embryonic rat hippocampal neuronal cultures through the activation of AMPK ( Ríos et al, 2018 ).…”
Section: Basal Autophagy and Neurogenesis During Developmentmentioning
confidence: 99%
“…Although WNT3A is not likely to pass through the BBB in an uninjured brain due to its size, the BBB is compromised in response to TBI and may be permissive to WNT3A uptake after intravenous injection [23]. On the other hand, intranasal delivery of proteins is believed to bypass the BBB in animal models [24], and our results demonstrate that this method of WNT3A delivery can produce a promising outcome on regeneration of injured brain neurons. The clinical efficacy of systemic or intranasal administration of protein drugs to the brain of TBI patients remains to be tested [25,26].…”
Section: Discussionmentioning
confidence: 66%